Influences of molecular structure on the isothermal crystallization behavior and mechanical properties of β-nucleated isotactic polypropylene. Issue 15 (12th October 2020) - Jiang, Weijiao; Song, Xiuduo; Zhou, Rui; Wu, Zongkai; Hu, Bo; Zhang, Yue; Liang, Zhiming; Chen, Zhengfang; Kang, Jian; Xiang, Ming
ABSTRACT: To investigate the influence of molecular structure of isotactic polypropylene (iPP) on the crystallization behavior and mechanical properties of its β-nucleated product, in this study, four iPP samples were selected. Results of molecular structure characterizations revealed that the molecular weight of the iPP resins are close, while the average isotacticities and the isotacticity distributions of the samples are quite different from each other. Isothermal crystallization kinetics study suggested that due to their different average isotacticities and isotacticity distributions, the crystallinity difference of the four samples is as high as 5.3%, and the crystallinity of β-crystal difference is as high as 7.2%. Generally, the higher the average isotacticity of the iPP and the wider its distribution are, the stronger the β-crystallization ability of the sample is. Moreover, the mechanical measurement revealed that high average isotacticity and the wide isotacticity distribution of the iPP resulted in the strong the β-crystallization ability and thus better the toughness. Graphical abstract: